Answer:
Explanation:
The average rate of change of a function over a given interval is the total change in the function's output (f(x)) divided by the total change in the input (x).
For the given table, the total change in x is 4 - (-2) = 6, and the total change in f(x) is 4 - (-8) = 12. The average rate of change is therefore 12/6 = 2.
So, the average rate of change of the function over the interval from x = -2 to x = 4 is 2. This means that, on average, the function's output (f(x)) changes by 2 units for every 1-unit change in the input (x).